On the Issue of Judges’ Salary as an Element of the Constitutional and Legal Status of Judges - V. S. Vitkova; Y. O. Hrabova (Bulletin of Kharkiv National University of Internal Affairs)
The article focuses on the use of the categories of «permanent population» and «existing population» while applying the regional coefficients in determining the basic amount of salary of a judge, since the judge’s salary guarantees the independence of the judge and is an integral part of his constitutional legal status. Attention is drawn to the fact that, since the judge’s salary can be determined only by the Law of Ukraine «On Judicial System and Status of Judges» the issue of the uniqueness of the application of regional coefficients requires an additional focus of scholars and practitioners, which, in turn, is related to the uncertainty of the provisions of paragraphs 2, 3, 4, Part 4 of the Art. 135 of the above mentioned Law. Determination of the regional coefficient for the calculation of the judge’s salary substantiates the feasibility of applying regional coefficients in practice based on the data, in particular, the basic indicators of the effectiveness of the courts of settlements, population of which exceed 1 million and total population of which is less than 100 thousand. Relevant comparative data on the burden on judges of such courts is provided. Based on the obtained empirical data, it is concluded that there are ambiguities in the use of the categories «existing population» and «permanent population» by the State Judicial Administration of Ukraine while approving staffing of courts in the period of 2017-2020 on the example of Odesa City, despite the relatively constant number of permanent and existing population in the city during this period. The necessity to apply the category of «existing population» in determining the basic salary of a judge is argued, as well as the advisability of amending the paragraphs 2-4 of Part 4 of the Art. 135 of the Law of Ukraine «On Judicial System and Status of Judges» in regard to the need for uniform application of this rule in practice and ensuring that the social guarantees of judicial independence are respected.